Landscapes of memory: The first visual images of the bororo of central Brazil - da Cunha, Edgar Teodoro [UNESP]; Novaes, Sylvia Caiuby (FapUNIFESP (SciELO), 2019)
The opportunity of exhibiting in a Bororo village in Central Brazil the film Matto Grosso, the Great Brazilian Wilderness (1931), and translating into Portuguese this typical travelogue and widely considered to be the first documentary with synchronized sound, led the authors to analyze visual images on the Bororo society made in the first decades of the XX century. The article focuses on how visual images – films and photographs - frequently show the intentions of the author and on the other hand may enhance memories and create a particular relationship with the past and history of a people.
Paisagens da memória: As primeiras imagens visuais dos Bororo do Brasil Central
Keywords: Bororo Indians; Brazil; Documentaries and travelogues; Penn Museum archive; Photographs; Visual anthropology